AB0718 Prevalence of risk factors for fractures in axial spondyloarthritis: a systematic review. (15th June 2017) - Ramírez, J García; Curbelo, R; Nieto, JC; Castañeda, S; Carmona, L
Abstract : Background: Spinal fractures occur more than expected in axial spondyloarthritis (Ax-Sp). However, it is not totally clear whether fracture risk depends solely on biomechanical problems of the spondyloarthritic spine or whether the prevalence of risk factors for fracture is larger than expected in these patients. Objectives: To describe the prevalence of risk factors for osteoporotic fractures (both axial and peripheral) in Ax-Sp. Methods: A systematic literature search was conducted. Medline, Embase and Cochrane Library databases were searched with a sensitive strategy including type of study and synonyms of Ax-Sp. All contemporary cross sectional studies or baseline results from representative cohorts of Ax-Sp published between January 2006 and 2016 were selected for detailed review. Only studies that fulfilled a minimum quality for survey data were included. Data on bone mineral density, prevalence of osteoporosis, and risk factor for fractures in Ax-Sp patients were collected. Results: After screening 3597 titles and abstracts, only 43 studies (34 cross-sectional, 3 prospective and 6 retrospective) were reviewed in detail. Of these, 20 studies compared Ax-Sp patients with a control group, either healthy individuals (17 studies) or subjects with other diseases (6 studies). Reported prevalence of osteoporosis varied from 2% to 39.6%. Alcohol intake (58–61%), use of corticosteroids (11.7–67%), and 25-OH vitamin D deficit (26–76%) were unexpectedly high in Ax-Sp patients. All other factors were within expected frequencies for a not too old population. Conclusions: Our systematic review found that alcohol intake, steroid use and 25-OH-vitamin D deficit should be taken into account when assessing comorbidity in Ax-Sp in order to avoid excess fractures. Acknowledgements: this project was funded by Merck Sharp & Dohme of Spain. Disclosure of Interest: None declared